Angle-closure glaucoma and aortic aneurysm - a case report - Lokchaitanya, Pujari; P., Manimekalai; Bharathi, Pon D.; Sainadh, Nandhyala D. V.; Prashanth, N. Lakshmi (International Journal of Advances in Medicine, 2023)
Acute angle closure glaucoma associated with an aortic aneurysm is common in familial cases. But it is uncommon without a positive family history. This article tells about a case of an 80-year-old female, who presented with complaints of severe eye pain, was diagnosed with angle closure glaucoma, and had an incidental finding of multiple aortic aneurysms. The patient was treated conservatively with medical management, and surgery was deferred due to age factor. It is important to know about this association to prevent complications and start prompt treatment.